Investigation into the Application of Image Modeling Technology in the Field of Computer Graphics - Doungmala, Pathasu; Thai, Thanh Hai (International Journal for Applied Information Management, 2023)
The field of computer graphics has experienced remarkable advancements in hardware and software, leading to rapid progress and development. One crucial aspect that significantly influences the authenticity and immersive nature of simulation environments is the utilization of image modeling technology. The success of creating realistic and captivating image modeling environments relies heavily on the effective implementation of this technology. In light of this, the present paper thoroughly examines the fundamental concepts of computer graphics and image modeling technology. Furthermore, it delves into an in-depth analysis of the integration of image modeling technology within the domain of computer graphics, followed by an exploration of the concealed algorithm behind its functioning. The continuous evolution of computer graphics systems, encompassing advancements in both hardware and software, has propelled the field forward at a remarkable pace. Among the various elements that contribute to the credibility and engagement of simulation environments, the utilization of image modeling technology stands out as a critical factor. This research paper endeavors to comprehensively investigate the fundamental principles of computer graphics and the intricate workings of image modeling technology. By dissecting and analyzing the conceptual framework of computer graphics and image modeling, the study sheds light on their interplay and interdependence. Finally, the paper unveils the concealed algorithm that underlies the operation of image modeling technology within the realm of computer graphics, thereby providing valuable insights into its inner workings.